2018
DOI: 10.1371/journal.pone.0205983
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia chaffeensis TRP47 enters the nucleus via a MYND-binding domain-dependent mechanism and predominantly binds enhancers of host genes associated with signal transduction, cytoskeletal organization, and immune response

Abstract: Ehrlichia chaffeensis is an obligately intracellular bacterium that establishes infection in mononuclear phagocytes through largely undefined reprogramming strategies including modulation of host gene transcription. In this study, we demonstrate that the E. chaffeensis effector TRP47 enters the host cell nucleus and binds regulatory regions of host genes relevant to infection. TRP47 was observed in the nucleus of E. chaffeensis-infected host cells, and nuclear localization was dependent on a variant MYND-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…TRPs also interact with nuclear proteins involved in Wnt target gene epigenetic modification and expression, including the Wnt response element transcriptional repressor TLE4 (102), co-activator DAZAP2 (103), and histone remodeling proteins ARID1B, KDM6B, and IRF2BP2 (104106). Furthermore, TRP32, TRP47, and TRP120 DNA-binding motifs are within the promoter region of numerous Wnt target genes, indicating the TRPs may directly influence Wnt gene transcription through nucleomodulin activity (3335). Although these specific interactions have not yet been investigated, it is likely that the nucleomodulin activity of TRP effectors or the recently discovered ubiquitin ligase activity of TRP120, plays a role in manipulation of these target proteins, facilitating Wnt pathway activity and ultimately enhancing E. chaffeensis intracellular survival (107).…”
Section: Intracellular Pathogensmentioning
confidence: 99%
“…TRPs also interact with nuclear proteins involved in Wnt target gene epigenetic modification and expression, including the Wnt response element transcriptional repressor TLE4 (102), co-activator DAZAP2 (103), and histone remodeling proteins ARID1B, KDM6B, and IRF2BP2 (104106). Furthermore, TRP32, TRP47, and TRP120 DNA-binding motifs are within the promoter region of numerous Wnt target genes, indicating the TRPs may directly influence Wnt gene transcription through nucleomodulin activity (3335). Although these specific interactions have not yet been investigated, it is likely that the nucleomodulin activity of TRP effectors or the recently discovered ubiquitin ligase activity of TRP120, plays a role in manipulation of these target proteins, facilitating Wnt pathway activity and ultimately enhancing E. chaffeensis intracellular survival (107).…”
Section: Intracellular Pathogensmentioning
confidence: 99%
“…These observations support the hypothesis of large-scale transcriptional alteration induced by Ank200 via mechanisms associated with the regulation of Alu-Sx elements. TRP32 and TRP120 bind to host-cell DNA at G-rich and G + C-rich motifs, respectively, as well as chromatin-associated proteins, such as histone methylases and demethylases, polycomb-group (PcG) proteins and other components of chromatin-remodeling complexes [43][44][45][46][47][48]. TRP120 acts as a transcriptional activator for host genes [44], while TRP32 activates or represses expression of its target genes [46,47].…”
Section: Ankyrin Repeat-and Tandem Repeat-containing Nucleomodulins: mentioning
confidence: 99%
“…TRP120 acts as a transcriptional activator for host genes [44], while TRP32 activates or represses expression of its target genes [46,47]. Recently, another TRP effector, TRP47, has been identified as a fourth E. chaffeensis nucleomodulin [48]. TRP47 translocates into the nucleus via a MYND (myeloid, Nervy, and DEAF-1)-binding domain and targets multiple infection-associated genes by binding DNA at G + C-rich motifs.…”
Section: Ankyrin Repeat-and Tandem Repeat-containing Nucleomodulins: mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have demonstrated that TRP has various interactions with host proteins in the regulation of biological processes. This major immunoreactive protein of E. chaffeensis interacts with multiple host proteins involved in posttranscriptional modification processes ( Lina et al., 2016 ; Kibler et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%